Market Discipline and Its Impact on Investment Intention: An Analysis of Information and Disclosure Factors - A Mukti Soma; Rizka Merryanti (International Journal of Marketing and Digital Creative, 2023)
This study aims to measure the effect of market discipline on investment intentions, using the Theory of Planned Behavior (TPB) and focusing on the information and reporting aspects, such as financial and accounting reports, statements from auditors, and disclosures. Non-Probability Sampling was used to survey 300 respondents, and the smartPLS application was used for data analysis. The findings reveal that investors' understanding of market discipline in information and disclosure aspects influenced their investment intention and disciplined excessive risk-taking behavior. However, this study is limited to a specific set of indicators and does not cover all aspects of market discipline, making it unique from previous studies.